Strengthening the Role of Village-Owned Enterprises Through Coaching in Rato Village, Lambu District, Bima Regency - Hendra, Hendra; Tasrif, Tasrif; Rijal, Muhammad Nur; Irfan, M.; Ardyansah, Ady; Taufiq, Muhammad; Arman, Arman; Lutfi, Muhamad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to evaluate the effectiveness of a health promotion activity in increasing public awareness of Clean and Healthy Living Behavior (PHBS) in Sakuru Village, Monta District, Bima Regency. The program was motivated by the low public awareness of the importance of PHBS, which contributes to the high prevalence of environment-related diseases, such as diarrhea and respiratory infections. The health promotion activity was conducted using a participatory approach, involving community leaders, housewives, and youth as change agents. The results indicate that the activity successfully improved the participants' knowledge and awareness of PHBS, with many participants starting to implement healthy behaviors, such as using proper sanitation facilities and managing waste. However, challenges remain in changing long-established habits. The evaluation suggests that the health promotion activity was effective in increasing public awareness, but sustained behavioral change requires continuous support from various stakeholders and collaboration between the government, community, and educational institutions.